2012
DOI: 10.1007/s00330-012-2705-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of meglumine gadoterate (Gd-DOTA)-enhanced MRI compared to unenhanced MRI in patients with chronic kidney disease (RESCUE study)

Abstract: ObjectiveTo prospectively compare the renal safety of meglumine gadoterate (Gd-DOTA)-enhanced magnetic resonance imaging (MRI) to a control group (unenhanced MRI) in high-risk patients.MethodsPatients with chronic kidney disease (CKD) scheduled for MRI procedures were screened. The primary endpoint was the percentage of patients with an elevation of serum creatinine levels, measured 72 ± 24 h after the MRI procedure, by at least 25 % or 44.2 μmol/l (0.5 mg/dl) from baseline. A non-inferiority margin of the bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…52 Second, gadolinium chelates should not be used routinely in pregnant women. Although no teratogenic or detrimental effects have been reported in animal studies, 9,[15][16][17]65,66 the challenge to clinical practice is the safety of transplacental passage of gadolinium-based contrast agents in the fetus, which has left many basic questions that are related to placental and fetal physiologic condition unexplored to date. 67 Gadolinium chelates may be used in pregnancy, in limited situations when the benefits outweigh the potential risks, for example in cases of suspected placenta accreta.…”
Section: Limitationsmentioning
confidence: 99%
“…52 Second, gadolinium chelates should not be used routinely in pregnant women. Although no teratogenic or detrimental effects have been reported in animal studies, 9,[15][16][17]65,66 the challenge to clinical practice is the safety of transplacental passage of gadolinium-based contrast agents in the fetus, which has left many basic questions that are related to placental and fetal physiologic condition unexplored to date. 67 Gadolinium chelates may be used in pregnancy, in limited situations when the benefits outweigh the potential risks, for example in cases of suspected placenta accreta.…”
Section: Limitationsmentioning
confidence: 99%
“…Our study had an average follow-up period for NSF of 25.8 months, and this follow-up duration is similar to previous studies that have monitored for NSF over a period of several months. 31 However, longer follow-up periods may be required to monitor for NSF given gadolinium's tissue residence of 4 to 11 months. 15 Though the sample size of this study is large enough to substantiate its results, its retrospective design without a control group comparison is a potential weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Within the last 3 years, two new molecular MRI agents have been approved for clinical use, exhibiting excellent safety profiles [104] . A recent report from the RESCUE study showed that gadolinium-DOTA did not affect the renal function and was a safe contrast agent in the patients with chronic kidney disease [105] . It must be noted, however, that even in the case of the targeted nanoparticles, most of the applied dose accumulates in the liver, spleen, kidneys and bladder.…”
Section: Challenges and Safety Considerationsmentioning
confidence: 99%